Two distinct types of color spreading induced by different luminance and color conditions in static flank transparency displays - Kimura, Eiji (Frontiers in Human Neuroscience, 2023)
Flank transparency refers to illusory, phenomenally transparent color spreading induced when narrow colored flanks are added to line segments located within a virtual region. We investigated whether the luminance conditions that induced flank transparency were consistent with predictions based on luminance-contrast-based boundary interactions and the episcotister model for perceptual transparency. Examination of the requirements for the boundary interaction and perceptual transparency revealed that similar luminance conditions are necessary for both; that is, the flank luminance needs to be intermediate between the line and background luminances. We used green and achromatic flanks and systematically varied the luminance of the flanks, line segments, and background. We then asked the observers to rate the subjective certainty of color spreading using a five-point scale. The results showed that the perception of color spreading depended on color as well as luminance conditions. Generally, color spreading was convincing and phenomenally transparent when luminance conditions were consistent with the requirements for boundary interaction and perceptual transparency. In addition, color conditions worked in a facilitatory and inhibitory manner. Moreover, the results revealed that another convincing color spreading could be observed when the flank luminance was lower than the line or background luminance, that is, when the luminance condition for perceptual transparency was not satisfied. The observers’ verbal reports indicated that phenomenal transparency was not evident in this color spreading. Overall, the present findings demonstrate that typical transparent color spreading is not the only one observed in the flank transparency display. Different color and luminance conditions can modulate the phenomenal appearance of color spreading, resulting in distinct types of color spreading.